Patient and caregiver preferences for haemophilia A treatments: A discrete choice experiment. Issue 6 (16th September 2020) - Su, Jun; Li, Nanxin; Joshi, Namita; Ng, Xinyi; Botteman, Marc; Shah, Rachel; Jain, Nisha; Lyn, Nicole; Preblick, Ronald
Abstract: Introduction: Long‐acting products are changing the haemophilia A treatment landscape by giving patients and caregivers treatment options with varying product attributes. Aim: A discrete choice experiment (DCE) was used to elicit treatment attribute preferences among patients with haemophilia A and caregivers of children with haemophilia A. Materials & methods: A survey of sociodemographics and preferences was completed by an online panel of adult patients with haemophilia A and caregivers of children (<18 years) with haemophilia A. The DCE included a series of questions in which respondents chose their preferred option from pairs of hypothetical treatment profiles with systematic variation in the levels of six attributes (safety concerns with too much clotting, bleed protection, dosing frequency, length of time the product has been approved for use, product type and joint health studies). Preference weights and relative attribute importance scores were estimated using random parameters logit models. Results: One hundred and thirteen patients (mean age: 35.5 years) and 96 caregivers (mean age of child: 10.3 years) were included. For patients with haemophilia A, the top three attributes ranked from the most to least important were: (a) dosing frequency; (b) bleed protection; and (c) safety concerns with too much clotting. For caregivers of children with haemophilia A, the ranking was as follows: (a) safety concerns; (b) bleed protection; and (c) dosing. Conclusions: Patients with haemophilia A viewed dosing as the most important driver of treatment decision‐making whereas caregivers of children with haemophilia A valued safety the most.